A Current Sensitivity Model for Power System Stability Studies - Miyahara Takahashi, Andre Luiz [UNESP]; Fortes, Elenilson de Vargas; Araujo, Percival Bueno de [UNESP]; Miotto, Ednei Luis; Barone Martins, Luis Fabiano; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
Mathematical models have an important role in the study, analysis and planning of electric power systems operation. Suitable models produce more reliable data regarding the real behavior of the system. The main objective of this article is to present a model for the study of power system small signal stability, the Current Sensitivity Model (CSM). The CSM is composed by sets of differential and algebraic equations. The differential equations are used to represent the dynamics of power systems equipment, such as generators and controllers. The algebraic equations represents the current nodal balance in all systems buses, where the current balance is the fundamental concept of the model. Simulations are performed in three test systems to evaluate CSM. In each of these simulations data obtained under CSM is compared with data obtained under Heffron and Phillips Model (HPM). The comparison allows to establish that for systems composed of a single machine connected to an infinite bus through a transmission line there are no differences between the models. For systems composed of more than one machine, defined as multimachine systems, numerical differences between CSM and HPM arises. Those differences are a result of the different concepts used to formulate the models, with the structure preservation being one of the key points, and one of the advantages of CSM over HPM.
Keywords: Current Sensitivity Model; Heffron and Phillips Model; Power System models; Small-signal Stability